Implementasi Total Quality Management Dalam Meningkatkan Mutu Lulusan Madrasah Aliyah Hidayatul Mubtadiin Jati Agung Lampung Selatan - Ani Renita Sari; Etika Pujianti; Nur Widiastuti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The purpose of this study is to explore and analyze the implementation of Total Quality Management (TQM) in improving the quality of graduates at Madrasah Aliyah Hidayatul Mubtadiin, Jati Agung, South Lampung, by emphasizing the integration of quality management practices, collective involvement of madrasah residents, and strengthening a collaborative culture. This study uses a qualitative approach with a single case study design to explore the implementation of Total Quality Management (TQM) in improving the quality of graduates at Madrasah Aliyah Hidayatul Mubtadiin, South Lampung. The research subjects included the madrasah principal, teachers, staff, and students, selected purposively. Data were collected through semi-structured interviews, participant observation, and curriculum documentation and evaluation reports. Analysis was conducted thematically with coding, categorization, and pattern identification. Validity was strengthened through triangulation of sources, methods, and member checking. This study shows that the implementation of Total Quality Management (TQM) at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung, South Lampung, significantly improves the quality of graduates through mutually supportive mechanisms. TQM encourages the collective involvement of all members of the madrasah community in planning, evaluation, and continuous improvement, strengthening a sense of responsibility and a participatory culture. The integration of quality management practices into the curriculum and learning process ensures clear quality standards, measurable performance indicators, and regular evaluation for continuous improvement. Furthermore, TQM fosters a collaborative culture and participatory communication among teachers and staff, enhancing shared ownership, transparency, and improving students' academic and social skills.